Mortalidad global y capacidad funcional anual de pacientes poscirugía de fractura de cadera - Carpio Tumba, Guillermo Manuel (2020)
Background: Low-energy hip fracture is the main complication of osteoporosis regarding mortality, disability and economic burden. To our knowledge, this would be the first study in a Ministry of Health hospital that evaluates mortality and functional capacity in patients with low-energy hip fracture who underwent surgery. Objectives: Determine mortality in patients with a low-energy hip fracture who underwent surgery. Methods: We performed an observational retrospective single-cohort study during the 2016-2019 period, formed by collecting operative notes of patients with hip fracture that underwent surgery. Patients under the age of 50 years and those with a secondary osteoporosis diagnosis were excluded. Results: We included 163 patients with a median age of 78.9 years ± 10.5. Mortality during the first 12 months after surgery was 13.5% and 30.67% at the end of the follow-up (mean of 28.91 months). We found higher mortality in men (38.78%), compared with women (27.19%). Likewise, 52.48% of patients were limited to perform vocational and avocational activities after the first year of surgery and 68.71% did not receive osteoporosis treatment after surgery. Conclusions: Low-energy hip fracture during the first 12 months after surgery is associated with a 13.5% mortality, higher than in general population, and a low functional capacity.